Immersive Decision-Making : A Quantitative Analysis of Metaverse Applications in Tourism Marketing - Mahesh Jain, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article investigates the transformative impact of metaverse-based virtualization on tourism marketing and consumer experiences. Through quantitative analysis of data collected via standardized questionnaires, we examine how virtual reality tours, 3D representations, and simulated experiences in the metaverse influence tourist decision-making processes and pre-travel engagement. Our findings reveal that metaverse applications significantly enhance tourists' ability to make informed decisions, reduce travel anxiety, and engage with personalized marketing content. The article demonstrates a positive correlation between virtual destination previews and increased consumer confidence, with 78% of respondents reporting higher satisfaction in their travel choices. Moreover, the study identifies a 35% reduction in pre-travel uncertainty among first-time visitors to unfamiliar destinations who utilized metaverse-based virtual tours. These results underscore the potential of metaverse technology to revolutionize tourism marketing strategies, offering implications for industry practitioners and paving the way for future research in digital tourism experiences.
Keywords: Metaverse Tourism; Virtual Reality Marketing; Digital Travel Experiences; Consumer Decision-Making; Destination Virtualization